High-Throughput Synthesis of Oligo(ε-caprolactone) / Oligotetrahydrofuran Based Polyurethanes. (5th April 2018) - Balk, M.; Lendlein, A.; Behl, M.
ABSTRACT: Robot assisted synthesis as part of high-throughput (HT) technology can assist in the creation of polymer libraries, e.g. polymers with a variety of molecular weights, by automatizing similar reactions. Especially for multiblock copolymers like polyurethanes (PUs) synthesized from telechels via polyaddition reaction, the adjustment of equivalent molar amounts of reactants requires a comprehensive investigation of end group functionality. In this work, PUs based on oligo(ε-caprolactone) (OCL) / oligotetrahydrofuran (OTHF) as model components were designed utilizing HT synthesis enabling the quantitative determination of the optimized ratio between reactive end-groups via fully automated syntheses without major characterization effort of end group functionality. The semi-crystalline oligomeric telechelics were connected with a diisocyanate and OCL with a molecular weight of 2, 4, or 8 kg∙mol -1 was integrated. Here, optimized molecular weights between 90 ± 10 kg∙mol -1 (in case of OCL 8 kg∙mol -1 ) and 260 ± 30 kg∙mol -1 (in case of OCL 2 kg∙mol -1 ) were obtained with an isocyanate content of 120 mol%, whereby 100 mol% of isocyanate groups resulted only in molecular weights between 60 ± 6 kg∙mol -1 (OCL 8 kg∙mol -1 ) and 80 ± 10 kg∙mol -1 (OCL 2 kg∙mol -1 ). In addition to the optimized ratio between isocyanate and hydroxy end groups, quantitative influences of the OCL chain length and overall molecular weights of PUs on thermal and mechanical properties were detected. The melting temperatures (Tm s) of OCL and OTHF domains were well separated for PUs of low molecular weight, the temperature interval between the Tm s decreased when the molecular weight of the PUs was increased, and were even overlapping towards one broad Tm, when OCL 2 kg∙mol -1 was incorporated. The storage modulus E' was highly dependent on OCL chain length exhibiting an increase with increasing molecular weight of OCL from 220 MPa to 440 MPa at 0 °C and decreased with increasing chain length of PUs. The elongation at break (εb ) was analyzed below and above Tm of OTHF resulting in εb = 780-870% at 0 °C and εb = 510-830% at 30 °C for PUs of high molecular weight. Accordingly, stretchability of PUs was almost independent of the state of OTHF (semi crystalline or amorphous) but correlated with the OCL precursor chain length (increasing εb with increasing chain length) and overall molecular weight of PUs (PUs at higher molecular weight exhibited higher εb ). Hence, the analysis of these quantitative influences between macromolecular structure of multiblock copolymers and the resulting properties (well separated Tm s versus overlapping melting transition, improvement of stretchability) would enable the design of new tailored PUs.